Data Security Technical and Organizational Protection Measures against Data Loss and Computer Crime - Lenhard, Thomas H. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
Using many practical examples and notes, the book offers an easy-to understand introduction to technical and organizational data security. It provides an insight into the technical knowledge that is mandatory for data protection officers. Data security is an inseparable part of data protection, which is becoming more and more important in our society. It can only be implemented effectively if there is an understanding of technical interrelationships and threats. This book is a translation of the original German 2nd edition Datensicherheit by Thomas H. Lenhard, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The Content How computers communicate - Dangers to data files - Technical threats - Dangerous software - Dangers from mobile devices - Dangers of phone systems - Destruction of data - Securing data - Encryption - Identification of computers - Firewalls - Configuration problems - DMZ - etc. The Target Groups (Future) data protection officers Lawyers who want to learn about data security Executives who would like to gain an insight into IT security Students of computer science and business informatics The Author Dr. Thomas H. Lenhard is an internationally recognized expert on information technology and data protection. He draws on a wealth of experience from three decades of data protection and data security.
Data protection and data security -- How computers communicate with each other -- What can happen to data files -- Technical threats -- Dangerous software -- Dangers from mobile data carriers and devices -- Telephone system as a source of danger -- Destruction of data -- Securing data -- Encryption -- Security of websites -- Common threats to IT security -- Identification of computers and IP addresses -- Firewalls -- Routers -- Configuration of protection systems -- The demilitarized zone -- Organizational data protection.
Keywords: Data protection; Computer science; Data and Information Security; Computer Science